Parking Space Demand Analysis in Majene City Park - Syamsiar, Nur Ratika; Asriana, Zul (Universitas Negeri Padang, 2023)
This research was conducted in Majene City Park which is located in Banggae District, Majene Regency, West Sulawesi Province is a city park that is often used by many people because of its advantageous location. This research aims to 1. Analyze the need for parking space in Majene City Park, 2. Know the parking space pattern in Majene City Park. The method used in this research is a field survey based on existing conditions and recording vehicles entering and exiting the parking lot. To ensure the physical state of the site, field research methodology was used to collect data for this study. To provide a sense of security to visitors, data analysis was carried out by providing an overview of the area by identifying the variables required for parking spaces and parking space patterns. The data was analyzed by calculating the amount of parking space requirements in Majene City Park. This takes into account the volume and accumulation of parking. Based on the findings of the investigation, a parking lot was found. It is expected that the government makes strategic planning in the regulation and management of parking levies in Majene City Park because parking lots are needed there. The results showed that the characteristics of Majene City Park include parking volume and accumulation.1) The busiest time for parking is between 20:00 and21:00, 2). Visitors accumulate the most peak parking on Sundays from 21:00 to 21:15, 3). From 20:00 to 21:00, the maximum parking capacity is available. The concept of parking space requirements is divided into 2, namely: 1. Parking spaces must be close to the road to make it easier for visitors, 2. Parking spaces are divided into 2 based on the type of vehicle.